Enhancing the social capital in industrial workplaces: Developing workplace interventions using intervention mapping. (February 2019) - Meng, Annette; Borg, Vilhelm; Clausen, Thomas
Highlights: A more practically feasible version of the intervention mapping method was developed. The adapted IM method is suitable to develop interventions at the workplace. More attention to the implementation of the action plans needs to be incorporated. Management plays and important role in the implementation of the action plans. Abstract: Social capital in the workplace has been found to be associated with employee wellbeing and work engagement. Yet, evidence of effects of interventions to enhance the social capital are lacking. The intervention mapping method has been described as a useful tool for developing workplace interventions but it is very resource consuming. We aimed to develop an adapted version of the intervention mapping method which is more practically feasible to apply. To get insight into strengths and weaknesses of the adapted method, we applied it and conducted interviews with staff at six companies. The interviews revealed that the action plans developed using the adapted intervention mapping method were generally perceived as relevant and that the action plans had a positive effect on the social capital. However, the implementation of the action plans had been a challenge. In conclusion, the adapted intervention mapping method appears to be suitable for developing interventions to enhance the social capital in the workplace. However, more attention to the implementation of the action plans needs to be incorporated into the method. Suggestions to enhance the implementation included the involvement of the management in the implementation and monitoring of the implementation of the action plans as well as integrating the action plans into existing procedures in the workplace.